Sri Lanka at the Crossroads of History (University College London, 2017)
The peoples of Sri Lanka have participated in far-flung trading networks, religious formations, and Asian and European empires for millennia. This interdisciplinary volume sets out to draw Sri Lanka into the field of Asian and Global History by showing how the latest wave of scholarship has explored the island as a 'crossroads', a place defined by its openness to movement across the Indian Ocean. Experts in the history, archaeology, literature and art of the island from c.500 BCE to c.1850 CE use Lankan material to explore a number of pressing scholarly debates. They address these matters from their varied disciplinary perspectives and diverse array of sources, critically assessing concepts such as ethnicity, cosmopolitanism and localisation, and elucidating the subtle ways in which the foreign may be resisted and embraced at the same time. The individual chapters, and the volume as a whole, are a welcome addition to the history and historiography of Sri Lanka, as well as studies of the Indian Ocean region, kingship, colonialism, imperialism, and early modernity.